A Cost Analysis of a Pancreatic Cancer Screening Protocol in High-Risk Populations - Bruenderman, Elizabeth (Am J Surg, 2015)
BACKGROUND: Pancreatic cancer is the 4(th) leading cause of cancer death in the U.S. A screening protocol is needed to catch early stage, resectable disease. This study suggests a protocol for high-risk individuals and assesses the cost in the context of the Affordable Care Act. METHODS: Medicare and national average pricing were used for cost analysis of a protocol using MRI/MRCP biannually in high-risk groups. RESULTS: ‘: Costs per year of life added’ based on Medicare and national average costs, respectively, are: $638.62 and $2542.37 for Peutz-Jehgers Syndrome, $945.33 and $3763.44 for Hereditary Pancreatitis, $1141.77 and $4545.45 for Familial Pancreatic Cancer and p16-Leiden mutations, and $356.42 and $1418.92 for new-onset diabetes over age 50 with weight loss or smoking. CONCLUSION: A screening program using MRI/MRCP is affordable in high-risk populations. The U.S. Preventive Services Task Force must reevaluate its pancreatic cancer screening guidelines to make screening more cost-effective for the individual.